2010
DOI: 10.1097/mao.0b013e3181f0c612
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Auditory Steady State Response Measurements During Vibrant Soundbridge Middle Ear Implantation in Patients With Mixed Hearing Loss

Abstract: Intraoperative ASSR measurement is a good method to study different positions of the FMT and to determine the best position of the FMT for a patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 11 publications
0
27
0
Order By: Relevance
“…Recently, the importance of intraoperative monitoring with CAP or auditory steady-state response for optimum FMT placement also has been highlighted, respectively, by Radeloff et al (25) in a preliminary study on 3 subjects and by Verhaegen et al (26).…”
Section: Improvements In Audibilitymentioning
confidence: 97%
“…Recently, the importance of intraoperative monitoring with CAP or auditory steady-state response for optimum FMT placement also has been highlighted, respectively, by Radeloff et al (25) in a preliminary study on 3 subjects and by Verhaegen et al (26).…”
Section: Improvements In Audibilitymentioning
confidence: 97%
“…Although many authors have reported on the usage of soft tissue material in RW implantations-mainly as a cushion 2,6,10,16,20,24,26,30,[32][33][34][35][36][37][38] -there has been some controversy regarding the effectiveness of this material in sound transfer. Rajan et al 39 showed that using a soft tissue coupler between the FMT and RWM resulted in less efficient coupling than when putting the FMT in direct (full or partial) contact with the RW membrane.…”
Section: Considerations/issuesmentioning
confidence: 99%
“…Verhaegen et al (2010) reported ASSR measurements in four subjects with severe mixed hearing loss for the intraoperative verification …”
Section: Analog and Direct Stimulationmentioning
confidence: 99%